Depressive symptoms among older adults pre- and post- COVID-19 pandemic - Ward, Mark; Kenny, Rose; Briggs, Robert (My University, 2021)
Objectives: It is a concern that public health measures to prevent older people contracting COVID-19 could lead to a rise in mental health problems such as depression. The aim of this study therefore is to examine trends of depressive symptoms before and during the COVID-19 pandemic in a large cohort of older people. Design: Observational study with 6-year follow-up. Setting & Participants: More than 3000 community-dwelling adults aged ≥60 years participating in The Irish Longitudinal Study on Ageing (TILDA). Methods: Mixed effects multilevel models were used to describe trends in depressive symptoms across 3 waves of TILDA: wave 4 (2016), wave 5 (2018), and a final wave conducted July-November 2020. Depressive symptoms were measured using the 8-item Center for Epidemiologic Studies Depression Scale (CES-D), with a score ≥9 indicating clinically significant symptoms. Results: The prevalence of clinically significant depressive symptoms at waves 4 and 5 was 7.2% [95% confidence interval (CI) 6.5, 7.9] and 7.2% (95% CI 6.5, 8.0), respectively. This more than doubled to 19.8% (95% CI 18.5, 21.2) during the COVID-19 pandemic. There was no change in CES-D scores between waves 4 and 5 (β = 0.09, 95% CI –0.04, 0.23), but a large increase in symptoms was observed during the pandemic (β = 2.20, 95% CI 2.07, 2.33). Age ≥70 years was independently associated with depressive symptoms (β = 0.45, 95% CI 0.18, 0.72) during the pandemic but not from wave 4 to 5 (β = 0.09, 95% CI –0.18, 0.36). Living with others was associated with a lower burden of symptoms during the pandemic (β = −0.40, 95% CI –0.71, −0.09) but not between waves 4 and 5 (β = −0.40, 95% CI –0.71, −0.09). Conclusions and Implications: This study demonstrates significant increases in the burden of depressive symptoms among older people during the COVID-19 pandemic, particularly those aged ≥70 years and/or living alone. Even a small increase in the incidence of late life depression can have major implications for health care systems and societies in general. Improving access to age-attuned mental health care should therefore be a priority.
PUBLISHED
Keywords: Depression; COVID-19; shielding; Ageing; Health